New Ordovician-Silurian drill cores from the Siljan impact structure in central Sweden: An integral part of the Swedish Deep Drilling Program - Lehnert, O.; Meinhold, G.; Bergström, S.; Calner, M.; Ebbestad, J.; Egenhoff, S.; FriskÅ, A.; Hannah, J.; Högström, A.; Huff, W.; Juhlin, Christopher; Maletz, J.; et al. (2012)
New drill cores from the largest known impact structure in Europe, the relict of the Siljan meteorite crater, provide new possibilities to reconstruct Early Palaeozoic marine environments and ecosystems, and to document changes in sedimentary facies, sea level and palaeoclimate in Baltoscandia. The impact crater is an important target of the project "Concentric Impact Structures in the Palaeozoic" within the framework of the "Swedish Deep Drilling Program". Two core sections, Mora 001 and Solberga 1, have been analysed. The sedimentary successions of these core sections include strata of late Tremadocian through late Wenlock ages. Our preliminary studies show not only that several of the classical Palaeozoic units of Sweden are represented in the area, but also that other significantly different facies are preserved in the Siljan district. An erosional unconformity representing a substantial hiatus occurs between Middle Ordovician limestone and a Llandovery-Wenlock (Silurian) shale succession in the western part of the Siljan structure and suggests an extended period of uplift and erosion. This may be related to forebulge migration due to flexural loading by the Caledonian thrust sheet to the west. Thus, this part of Sweden, previously regarded as a stable cratonic area, presumably was affected by the Caledonian collision between Baltica and Laurentia. © 2012 Copyright Geologiska Föreningen.